TEACHING AIDS FOR TEACHING ABOUT ELECTRICITY - DOSOUDIL, Jakub (Trends in education, 2012)
An integral part of technology in elementary schools is the area of physics and practical activities. There is currently possible to teach topics related to electricity. Since the laws of electricity and its related discipline the uneasy rather abstract phenomenon, to which the students can't touch, you need to use in the classroom the teaching aids. Without teaching aids students would be hard to understand topics. In this article we aim to compare of all the options the use of teaching aids, utilities compare themselves, evaluate their pros and cons and choose the best ones.
Keywords: teaching aids; physics; electricity.